2016
DOI: 10.1589/jpts.28.2220
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hippotherapy on postural balance and functional ability in children with cerebral palsy

Abstract: [Purpose] This study evaluated the effects of hippotherapy on seated postural balance, dynamic balance, and functional performance in children with cerebral palsy and compared the effects of 12 and 24 sessions on seated postural balance. [Subjects and Methods] This study included 15 children with cerebral palsy aged between 5 and 10 years. Interventions: A hippotherapy protocol was performed for 30 minutes, twice a week, for 12 weeks. Postural balance in a sitting position was measured using an AMTI AccuSway P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
1
23
0
12
Order By: Relevance
“…As a result of this phenomenon, it was found that horseback riding led to a statistically significant improvement measured by BBS in stroke patients , and that 24 sessions of hippotherapy led to statistically significant improvement in the balance in the sitting position and dynamic balance in children with cerebral palsy (Moraes et al, 2016). This results are thought that hippotherapy led to similar improvements at the statistically significant level in the BBS and TUG tests in the present study conducted with children with intellectual disabilities by adjusting anticipatory postural control and reactive postural control to maintain the alignment of the body on a horse.…”
Section: ⅳ Discussionmentioning
confidence: 95%
“…As a result of this phenomenon, it was found that horseback riding led to a statistically significant improvement measured by BBS in stroke patients , and that 24 sessions of hippotherapy led to statistically significant improvement in the balance in the sitting position and dynamic balance in children with cerebral palsy (Moraes et al, 2016). This results are thought that hippotherapy led to similar improvements at the statistically significant level in the BBS and TUG tests in the present study conducted with children with intellectual disabilities by adjusting anticipatory postural control and reactive postural control to maintain the alignment of the body on a horse.…”
Section: ⅳ Discussionmentioning
confidence: 95%
“…Los autores concluyen que un programa de hipoterapia durante 10 semanas puede mejorar las funciones corporales y la ejecución de actividades de motricidad gruesa y fina en los niños con PC. Moraes et al (2016) evaluaron los efectos de 12 y 24 sesiones de hipoterapia en el equilibrio postural sentado, el equilibrio dinámico, y el rendimiento funcional en 15 niños con PC con edades comprendidas entre los 5 y 10 años. El protocolo de hipoterapia se realizó durante 30 minutos, dos veces a la semana, durante 12 semanas, midiendo el equilibrio postural en posición sentada utilizando una plataforma de fuerza AMTI AccuSway Plus 1 semana antes de iniciar el programa de hipoterapia y después de 12 y 24 semanas.…”
Section: Resultsunclassified
“…Η κλίμακα ισορροπίας Berg (BBS) και η (PEDI) χρησιμοποιήθηκαν πριν και μετά τις συνεδρίες. Και οι δυο ομάδες εμφάνισαν βελτίωση και περισσότερο εκείνη των 24 συνεδριών στην ισορροπία της στάσης, στη δυναμική ισορροπία και τη λειτουργικότητα (Moraes, Copetti & Angelo, 2016).…”
Section: αποτελέσματαunclassified